2021
DOI: 10.1177/10497323211026914
|View full text |Cite
|
Sign up to set email alerts
|

The Lived Experience of a Newly Diagnosed Older Person With HIV in Ukraine

Abstract: Low- and middle-income countries are home to 80% of older people with HIV (OPWH). Ukrainian OPWH experience higher mortality and decreased antiretroviral therapy (ART) initiation than younger patients, but there is little data examining OPWH’s perspectives around new diagnosis and impact on care. In this study, we examined accounts of 30 newly diagnosed OPWH in Ukraine, exploring challenges faced in the peri-diagnosis period. Themes emerged representing the longitudinal coping process: OPWH (1) viewed themselv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…Studies that have examined the lives of these patients have shown that these patients will experience mental and living problems throughout their lives. These studies highlight the need for age-specific programming to increase HIV knowledge and coping, increase screening, and improve long-term planning [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies that have examined the lives of these patients have shown that these patients will experience mental and living problems throughout their lives. These studies highlight the need for age-specific programming to increase HIV knowledge and coping, increase screening, and improve long-term planning [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence of HCPs in many countries disclosing people’s HIV status without consent [ 5 ]. Consequently, fears of breaches in confidentiality lead to PLWH not disclosing their HIV status to their primary care providers [ 17 , 18 ]. A study that involved interviewing 79 PLWH in Albania found that 97.4% reported fear of disclosure of their HIV status as a barrier to accessing HIV care [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this finding that women experience more GAD and depression than their male counterparts may reflect similar findings elsewhere in LMIC settings before COVID [ 56 , 57 ]. Additional contributors to elevated mental health concerns may relate to findings in Ukraine that suggest that HIV stigma contributes to worse mental health [ 58 ], and because women reflect relatively lower levels of HIV than their male counterparts, their mental health may be affected by minority stress [ 59 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%